Strategi Komunikasi Global Dalam Praktik Pemasaran Global - Jubaidah, Siti; Pasaribu, Yogi Oriena; Nurleli, Nurleli; Suhairi, Suhairi (Fakultas Sains & Teknologi, Universitas Labuhanbatu, 2024)
This research is based on the desire to analyze the role of global communication strategies in current global marketing practices where competition is high. The analytical tool is a qualitative method used by the author, namely to fill in the data or information collected with the final result in the form of writing. This method is used to describe and explain management strategies for dealing with waqf problems through collecting information and studying documents, such as e-books, journal articles and papers. The ideas that will be put forward highlight: first, the concept of global marketing communications; second, variables that influence global communication; third, global marketing communications strategy; fourth, the benefits of global marketing communications. The research results concluded that the marketing activities implemented were based on a planned strategy design based on the results of an analysis of the competitive conditions of a product's industry at various levels of the product life cycle, which needed to be communicated between the company and the target market. In this activity, global marketing communication is very important, because through appropriate marketing communication in accordance with culture, life style, buying habits, consumer consumption patterns, communication media, target consumers.